Lei nº 10.639/2003 - deslocamentos discursivos sobre a educação das relações raciais no Brasil: tensões e silenciamentos no contexto escolar da rede pública de Belo Horizonte. - Silvia Regina de Jesus Costa (2017)
This research is of qualitative nature and aims to analyze the discourses of educators on racial and ethnic relations in the Brazilian school context in a broader perspective. The participants in the study were teachers, pedagogical coordinators, supervisors and one female librarian from two public schools in the outskirts of Belo Horizonte, in the state of Minas Gerais. More than ten years have passed since the publication of Law 10639/2003, which deals with the compulsory education of racial and ethnic diversity in schools, and the discourses and discursive practices of the subjects that promote the teaching-learning process reverberate different racial discourses, reflecting, in the school context, the discourse of racial relations in Brazil. Thus, they also reflect the ideological formation accessed, the historical and sociological foundations that are being (de) constructed in the implementation of the Law. In order to verify the data collected, we used methodological procedures, such as questionnaires, semi-structured interviews and focus group. The written work was constituted in two parts: First, we sought to elaborate a brief bibliographic review on the discourses of racial relations between the nineteenth and early twentieth centuries of Brazilian history and sociology. Along with the review, a brief theoretical survey was developed on some concepts that comprise the Critical Discourse Analysis (CDA), Discourse Analysis (DA) and some theoretical constructs from Bakhtin (1992). With the history and sociology of race relations, we have listed some discourses that reverberate through the subjects: The Whitening Ideology, Myth of Racial Democracy, The Race and Class Discourse, and counter-discourses or counter-hegemonic discourses. In a second moment, we selected the speeches, prioritizing the relations with the racial issue. Through the collected data, we have seen several developments in the discourses on race relations, punctuated in Brazilian history and sociology. Ideologies constitute the representations of the ideas of society, which guide social, moral, ethical values, individual behaviors, generating a civilizing parameter. The hegemonic ideologies are those that have the greatest impact and expression in social relations. However, they are voices that resist and generate contradictions against injustices and social inequalities through the immediate context. The whitening ideology reverberated through the enunciation certain types of exclusions. The investigation subjects presented a discourse of recognition of the mechanisms that generate the social hierarchies through the cultural and behavioral characteristics, and phenotype aspects. As a social mechanism of exclusion, issues such as black youth genocide, the prison system and drug dealing were identified in the speeches of those who seek to eliminate the black population from society. As social hierarchies, the discrimination against the Afro-Brazilian culture, clothes, dances and behaviors related to black youth were pointed out. In order to denote the hierarchies based on the phenotypic characteristics, the investigation subjects punctuated the attitudes of the students in uttering adjectives that make blacks inferior. The myth of racial democracy has been shaped by hybridism that have punctuated a supposed racial equality. Whether through the silencing of prejudices or discrimination that cross the school context; or by the denial of the inherent differences to the subjects that engender the school relations, the discourse that was forged through economic class ideology is sustained through the silencing of race as an element that structures social relations in Brazil.